Climate change and vulnerability of paddy cultivation in north-west Selangor, Malaysia: a survey of farmers' assessment / Md. Mahmudul Alam... [et al.] - Alam, Md. Mahmudul; Siwar, Chamhuri; Islam, Rafiqul; Toriman, Mohd Ekhwan; Basri, Talib (Universiti Teknologi MARA, Kedah, 2011)
Climate and agriculture highly interrelated. Agriculture is highly dependent on the climatic factors. The climatic factors as well as other factors that are determined by climate cause vulnerability of agriculture and agricultural production.. Using a survey method this study aims to determine the impacts of climatic change on agricultural vulnerability in the Integrated Agricultural Development Area (IADA), West Selangor, Malaysia. Results suggest that over the last 5 years vulnerability of the factors like, injurious insects, high temperature, soil fertility loss, and cost of input materials increased greatly due to climatic changes; and the vulnerability of the factors like shortage of rainfall, excessive rainfall, and labor scarcity increased moderately during this period. It is projected that due to climate change agricultural production sustainability will become vulnerable in Malaysia by 2020.